Study of the volatile compounds of dry fermented sausage with salt reduction and its relationship with sensory acceptance - de Almeida, Marcio Aurélio (2024)
In many industrialised countries, sodium intake exceeds the nutritional guidelines. High sodium intake has been associated with health problems, such as arterial hypertension and, consequently, a higher health risk of cardiovascular disease. The aim of this study was to evaluate overall quality of salamis with reduced sodium content by analysing aldehydes, proteolysis, and lipolysis, as well as to verify the correlation between sensory acceptance and volatile compounds. Four formulations were prepared replacing NaCl by a mixture of KCI and CaCl2. Two controls, one with a highlevel and the other with a low NaCl level were also included in the study. Water activity and pH levels were monitored in all samples. Volatile compounds were measured, in particular, hexanal, 2,4-decadienal and 3-methylbutanal. Finally, a sensory acceptance test was carried out using potential consumers. The results highlighted a relation between aldehyde concentration and sensory acceptance, hexanal/3-methybutanal ratio, that may be a marker of partial NaCl ubstitution in salami. Thus, our results may be used to guide the use of NaCl substitution by KCl/CaCl2 in terms of volatile compounds.